2004
DOI: 10.1539/joh.46.43
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Psychological Job Demands in a Bus Driver Sample

Abstract: External Validation of Psychological Job Demands in a Bus Driver Sample: David Gimeno, et al. Occupational Health Research Unit. Department of Health and Experimental Sciences, Universitat Pompeu Fabra, Spain—Psychosocial risk factors have been considered as characteristics of the work environment rather than an individual issue, but their presence in the workplace is usually measured by self‐reported questionnaires, based on worker attitudes. The objective of the study was to compare a self‐reported measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…Several studies on occupational stress adopted both subjective and objective methods to evaluate job stressors and strain 19,[21][22][23][24][25][26][27] . All the studies found some correlation between subjective and objective measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on occupational stress adopted both subjective and objective methods to evaluate job stressors and strain 19,[21][22][23][24][25][26][27] . All the studies found some correlation between subjective and objective measures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evaluation of job stress should result from an integration of subjective and objective measures of stressors, strain and health outcomes. An integrated assessment of job-stress was applied in this study to a group of hospital workers, and compared to similar experiences on health care workers [21][22][23] and workers from other sectors 19,[24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…The Job Content Questionnaire (JCQ), a valid and reliable instrument [Karasek et al, 1998;Ostry et al, 2001;Landsbergis et al, 2002;Gimeno et al, 2004], was utilized in the questionnaire to assess demand, control, and support dimensions. One question (conflicting demands) was reworded and reversed.…”
Section: Self-reported Datamentioning
confidence: 99%
“…Por otro lado, también se utilizaron algunos correlatos (Del-Líbano et al, 2010) o también denominados indicadores externos (Gimeno, Benavides, Mira, Martínez y Benach, 2004) en forma de preguntas que los informantes debían de contestar. Algunas de ellas hacían referencia a "En términos generales, ¿te sientes saludable?…”
Section: Instrumentosunclassified